MENGEFEKTIFKAN PENGELOLAAN ASET DAERAH MELALUI PEMBELAJARAN ORGANISASIONAL: Mediasi Job Crafting sebagai Faktor Kunci - Syamsul Alam; Zulfiah Larisu; Faturachman Alputra Sudirman; Taufik; La Ode Herman Halika (Journal Publicuho, 2024)
This study aims to explore the role of organizational learning and job crafting in enhancing the effectiveness of asset management in South Konawe Regency. The primary issue addressed is the low effectiveness in asset management aspects, such as planning, procurement, utilization, assessment, and administration. This research examines how individuals, through job crafting, can improve asset management performance and support more effective organizational learning. Data were collected through in-depth interviews, document studies, and observations at the Regional Financial and Asset Management Agency, as well as related agencies such as the Education and Health Offices. The findings indicate that limited organizational learning and a lack of policies supporting collaboration and the use of technology hinder asset management effectiveness. Job crafting, focusing on task crafting, relational crafting, and cognitive crafting, can improve collaboration and enhance employees' understanding of their contributions to organizational goals. This study suggests that policies should better support team-based learning, technology, and cross-unit collaboration. Leadership must also promote job crafting implementation to boost employee motivation and commitment to more efficient asset management. This research is expected to provide a foundation for better policies and encourage more efficient and sustainable asset management practices in the future.